2014
DOI: 10.1149/2.0071501eel
|View full text |Cite
|
Sign up to set email alerts
|

Field-Limited Migration of Li-Ions in Li-Ion Battery

Abstract: The migration of Li-ions in lithium-ion battery cannot be simply described by Fick's second law; the interactions among ionic migration, field, and stress need to be taken into account when analyzing the migration of Li-ions. Using the theory of thermal activation process, the flux for ionic migration under concurrent action of electric field and mechanical stress is found to be a nonlinear function of the gradient of electric potential and the gradient of stress. Electric field can either accelerate or retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…So the Si–C interfaces effectively promote the diffusion kinetics of Li-ions along the D ⊥ in Si/C multilayer electrodes. It should be a result of the local polarization of lithiated Si (Li x Si) located at the Si–C interface under an applied electric field. Li x Si alloy preferentially nucleates and grows at the Si–C interfaces, and its conductivity is much higher than that of Si. As schematically illustrated in Figure , introducing a conducting sphere into a static electric field causes the charges inside the sphere to quickly redistribute near the surface, so that the electric field inside the sphere becomes zero due to the polarization of the sphere, but the local external field becomes stronger.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So the Si–C interfaces effectively promote the diffusion kinetics of Li-ions along the D ⊥ in Si/C multilayer electrodes. It should be a result of the local polarization of lithiated Si (Li x Si) located at the Si–C interface under an applied electric field. Li x Si alloy preferentially nucleates and grows at the Si–C interfaces, and its conductivity is much higher than that of Si. As schematically illustrated in Figure , introducing a conducting sphere into a static electric field causes the charges inside the sphere to quickly redistribute near the surface, so that the electric field inside the sphere becomes zero due to the polarization of the sphere, but the local external field becomes stronger.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The interfacial diffusion pathway of Li-ions differs from the surface-coating directed Li-ions transport and the Se nanowires confined in carbon shows a significantly improved rate capability and cyclic performance. Theoretical calculations combined with experimental research have shown that an unbalanced charge distribution induced a built-in electric field within the CuGeO 3 /graphene, SnS/SnO 2 , and MnO 4 /Bi 2 O 2 heterointerfaces that can boost Li-ions diffusion kinetics and promote rate capability. The built-in electric field within heterointerfaces can either accelerate or retard the Li-ions diffusion, as reported by Yang …”
mentioning
confidence: 85%
See 1 more Smart Citation
“…To in-depth understand the advantage of multilayered Si/C anodes for high-rate LIB applications, three possible mechanisms are proposed as follows. (1) The enhanced local electric fields by Li x Si alloys formed at Si–C interfaces play a starring role in boosting the performance. It is reported that the Li x Si alloys prefer to nucleate and grow at Si–C interfaces under the applied electric field, resulting in the local polarization of Li x Si alloys at the interfaces. , As illustrated in Figure a, the conductive Li x Si alloy spheres in a static electric field can make the charge redistribution and local polarization near the sphere surfaces, leading to a zero electric field inside the spheres and a stronger local external field. As a result, the locally coupled built-in electric field promotes the Li + ion diffusion in the multilayered Si/C film anodes .…”
Section: Results and Discussionmentioning
confidence: 99%
“…(1) The enhanced local electric fields by Li x Si alloys formed at Si−C interfaces play a starring role in boosting the performance. It is reported that the Li x Si alloys prefer to nucleate and grow at Si−C interfaces under the applied electric field, 58 resulting in the local polarization of Li x Si alloys at the interfaces. 59,60 As illustrated in Figure 6a, the conductive Li x Si alloy spheres in a static electric field can make the charge redistribution and local polarization near the sphere surfaces, leading to a zero electric field inside the spheres and a stronger local external field.…”
mentioning
confidence: 99%